Respuesta :

Answer:

The final simplification is (32p^-15).

Step-by-step explanation:

Given:

(2p^-3)^5 we have to simplify.

Property to be used:(Power rule)

Power rule states that: [tex](a^x)^y=a^x^y[/tex] ...the exponents were multiplied.

Using power rule.

We have,

⇒[tex](2p^-3)^5[/tex]          

⇒[tex](2^5)(p^-3^*5)[/tex]     ...taking exponents individually.

⇒[tex]32(p^-^1^5)[/tex]         ...[tex]2^5=2*2*2*2*2=32[/tex]

⇒[tex]32p^-^1^5[/tex]

So our final values are 32p^-15

ACCESS MORE